Structural analysis of the α‐glucosidase HaG provides new insights into substrate specificity and catalytic mechanism. (1st June 2015) - Shen, Xing; Saburi, Wataru; Gai, Zuoqi; Kato, Koji; Ojima‐Kato, Teruyo; Yu, Jian; Komoda, Keisuke; Kido, Yusuke; Matsui, Hirokazu; Mori, Haruhide; Yao, Min
<x xml:space="preserve">Abstract</x> α‐Glucosidases, which catalyze the hydrolysis of the α‐glucosidic linkage at the nonreducing end of the substrate, are important for the metabolism of α‐glucosides. Halomonas sp. H11 α‐glucosidase (HaG), belonging to glycoside hydrolase family 13 (GH13), only has high hydrolytic activity towards the α‐(1→4)‐linked disaccharide maltose among naturally occurring substrates. Although several three‐dimensional structures of GH13 members have been solved, the disaccharide specificity and α‐(1→4) recognition mechanism of α‐glucosidase are unclear owing to a lack of corresponding substrate‐bound structures. In this study, four crystal structures of HaG were solved: the apo form, the glucosyl‐enzyme intermediate complex, the E271Q mutant in complex with its natural substrate maltose and a complex of the D202N mutant with D‐glucose and glycerol. These structures explicitly provide insights into the substrate specificity and catalytic mechanism of HaG. A peculiar long β→α loop 4 which exists in α‐glucosidase is responsible for the strict recognition of disaccharides owing to steric hindrance. Two residues, Thr203 and Phe297, assisted with Gly228, were found to determine the glycosidic linkage specificity of the substrate at subsite +1. Furthermore, an explanation of the α‐glucosidase reaction mechanism is proposed based on the glucosyl‐enzyme intermediate structure.